Saint Joan. - Shaw Bernard (penguin, 1951)
Cort Theatre, The Theatre Guild presents Uta Hagen in Margaret Webster's production of Bernard Shaw's "Saint Joan," with John Buckmaster, Andrew Cruickshank, Alexander Scourby, Robert Pastene, Frederic Worlock, directed by Miss Webster, scenery designed by Richard Harrison Senie, costumes designed by Elinor Robbins, original score by Lehman Engel, production under the supervision of Theresa Helburn and Lawrence Langner.